2019
DOI: 10.1007/s00394-019-02106-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food-related behavioral activation therapy on food intake and the environmental impact of the diet: results from the MooDFOOD prevention trial

Abstract: Purpose Food-based dietary guidelines are proposed to not only improve diet quality, but to also reduce the environmental impact of diets. The aim of our study was to investigate whether food-related behavioral activation therapy (F-BA) applying Mediterranean-style dietary guidelines altered food intake and the environmental impact of the diet in overweight adults with subsyndromal symptoms of depression. Methods In total 744 adults who either received the F-BA intervention (F-BA group) or no intervention (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 55 publications
(84 reference statements)
2
42
0
Order By: Relevance
“…Although the F‐BA promoted an n‐3 PUFA rich diet (e.g., three times of fish per week), F‐BA did not lead to changes in PUFA serum levels, as the groups with F‐BA did not have significantly higher n‐3 PUFA, DHA, or EPA levels or lower n‐6 PUFA levels at 6‐ or 12‐month follow‐up when compared to the groups without F‐BA, except for higher DHA levels at 6 months of follow‐up in the group with placebo and F‐BA. The fact that we did not find a consistent increase in all n‐3 PUFA measures and at all time points was unexpected, because a self‐reported increased intake of food products high in n‐3 PUFAs (e.g., fatty fish, nuts, and seeds) in the F‐BA groups was found previously in the same MooDFOOD study sample (Grasso et al, 2019). It seems like the increase of intake of products high in n‐3 PUFAs was only moderate and therefore may not have led to substantial increases in all n‐3 PUFAs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although the F‐BA promoted an n‐3 PUFA rich diet (e.g., three times of fish per week), F‐BA did not lead to changes in PUFA serum levels, as the groups with F‐BA did not have significantly higher n‐3 PUFA, DHA, or EPA levels or lower n‐6 PUFA levels at 6‐ or 12‐month follow‐up when compared to the groups without F‐BA, except for higher DHA levels at 6 months of follow‐up in the group with placebo and F‐BA. The fact that we did not find a consistent increase in all n‐3 PUFA measures and at all time points was unexpected, because a self‐reported increased intake of food products high in n‐3 PUFAs (e.g., fatty fish, nuts, and seeds) in the F‐BA groups was found previously in the same MooDFOOD study sample (Grasso et al, 2019). It seems like the increase of intake of products high in n‐3 PUFAs was only moderate and therefore may not have led to substantial increases in all n‐3 PUFAs.…”
Section: Discussionsupporting
confidence: 53%
“…Fortunately, included and excluded participants did not differ on the severity of depression. Analyses did not further consider food intake, but at baseline, our intervention groups did not differ (Grasso et al, 2019) on this factor. As there is no universally agreed/golden standard reference range for PUFA levels, and as this also depends on measurement aspects including laboratory‐specific analytical procedures, a reference range for low versus high PUFA levels cannot be given or used in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are ostensibly to some extent contrary to our findings published elsewhere on the effect of the F-BA on food intake using a self-reported food frequency questionnaire. 18 In that analysis, the F-BA changed the eating behaviour for a number of food groups (eg, increasing fruit and vegetable consumption, whole grains and fish; decreasing the consumption of sugary snacks) but for not for others (eg, reducing meat, alcoholic beverages, high fat dairy and soft drinks). It should be noted that in the present study, the questionnaire used to assess the F-BA was tapping into beliefs about the successfulness of the strategies used while the food frequency questionnaire, although self-report, is effectively a count of actual food consumed over a given period.…”
Section: Discussionmentioning
confidence: 99%
“…The MooDFOOD Trial found that while neither intervention had significant effects on incidence of MDE over 12 months, 17 F-BA, relative to no F-BA, reduced symptoms of depression at 12 months follow-up for those with higher initial severity and prevented MDE for those with higher levels of treatment adherence, 17 as well as reducing unhealthy food consumption and increasing healthy food consumption. 18 There were no beneficial effects of daily nutrient supplementation on depressive symptoms, and there was even evidence that outcomes were worse for those taking supplements versus placebo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation